La Population Syndiquée au Québe - Lipsig-Mumme, Caria; Roy, Rita (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1989)
Abstract Who is an organized worker today in Québec? After a review of the main changes in the labour market since 1975 in three main areas: feminization, precarisation and tertiarisation, this article portrays the internal characteristics of the organized population. The authors then go on to compare organized and unorganized workers with the potential labour force regarding their age, sex, education, work status and average wage. They conclude that the organized population is relatively older, that men are over-represented, that it enjoys better job security, relatively high wages, and sectorial concentration. Finally, the article attempts to throw some light on the impact of new demographic parameters on the difficult strategic repositioning being crystaliscd in the Québec labour movement. Rough Work and Rugged Men: